(untitled) (Mansfield, Mass., 1980)
Data acquisition and conversion systems interface between the real world of physical parameters which are analog and the artificial world of digital computation and control.
Keywords: Kỹ thuật tương tự,Kỹ thuật số,Digital,Analog; Kỹ thuật số,Kỹ thuật tương tự,Analog,Digital